Direct comparison of Hoxb8-driven reporter distribution in the brains of four transgenic mouse lines: towards a spinofugal projection atlas - Barraclough, Bridget N.; Stubbs, W. Terrence; Bohic, Manon; Upadhyay, Aman; Abraira, Victoria E.; Ramer, Matt S. (Frontiers in Neuroanatomy, 2024)
Introduction Hox genes govern rostro-caudal identity along the developing spinal cord, which has a well-defined division of function between dorsal (sensory) and ventral (motor) halves. Here we exploit developmental Hoxb8 expression, normally restricted to the dorsal cord below the obex, to genetically label spinal cord-to-brain (“spinofugal”) axons. Methods We crossed two targeted (knock-in) and two non-targeted recombinase-expressing lines (Hoxb8-IRES-Cre and Hoxb8-T2AFlpO; Hoxb8-Cre and Hoxb8-FlpO, respectively) with appropriate tdtomato-expressing reporter strains. Serial sectioning, confocal and superresolution microscopy, as well as light-sheet imaging was used to reveal robust labeling of ascending axons and their terminals in expected and unexpected regions. Results This strategy provides unprecedented anatomical detail of ascending spinal tracts anterior to the brainstem, and reveals a previously undescribed decussating tract in the ventral hypothalamus (the spinofugal hypothalamic decussating tract, or shxt). The absence of Hoxb8-suppressing elements led to multiple instances of ectopic reporter expression in Hoxb8-Cre mice (retinal ganglion and vomeronasal axons, anterior thalamic nuclei and their projections to the anterior cingulate and retrosplenial cortices and subiculum, and a population of astrocytes at the cephalic flexure) and Hoxb8-FlpO mice (Cajal–Retzius cells of the dentate gyrus, and mesenchymal cells of the choroid plexus). While targeted transgenic lines were similar in terms of known spinofugal projections, Hoxb8-IRES-Cre reporters had an additional projection to the core of the facial motor nucleus, and more abundant Hoxb8-lineage microglia scattered throughout the brain than Hoxb8-T2A-FlpO (or any other) mice, suggesting dysregulated Hoxb8-driven reporter expression in one or both lines. Discussion This work complements structural and connectivity atlases of the mouse central nervous system, and provides a platform upon which their reactions to injury or disease can be studied. Ectopic Hoxb8-driven recombinase expression may also be a useful tool to study structure and function of other cell populations in non-targeted lines.